Cognitive perspective-taking during scene perception in autism spectrum disorder: Evidence from eye movements - Au-Yeung, SK; Kaakinen, JK; Benson, V (Wiley, 2013)
The present study examined how eye movements during scene viewing are modulated by adopting psychological perspectives in both adults with autism spectrum disorders (ASD) and typically developing adults. In the current study, participants viewed house scenes with either non‐perspective‐taking (look for valuable items/features of the house that need fixing) or perspective‐taking instructions (imagine that you are a burglar/repairman) while their eye movements were recorded. The eye movement measures revealed that for the “look for the valuable items” and burglar perspective task, the ASD group showed typical relevance effects (the preference to look at schema‐relevant compared with schema‐irrelevant targets) in their eye movements. However, we found subtle processing differences between the groups that were related to initial orienting to and processing of schema‐relevant items for the “look for the features that need fixing” and the repairman perspective‐taking task. There was an absence of a relevance effect for the ASD group for the repairman perspective and its non‐perspective‐taking equivalent instruction showing that the identification of items relevant to those schemas was more difficult for the ASD group. The present findings suggest that resolving ambiguity may be a defining feature of complex information processing deficits in ASD.